SURG-12. PREDICTORS OF SURVIVAL AND UTILITY OF INTRAOPERATIVE MRI FOR RESECTION OF GRADE II ASTROCYTOMAS AND OLIGODENDROGLIOMAS: A MULTICENTER ANALYSIS. (9th November 2020) - Yahanda, Alexander; Patel, Bhuvic; Shah, Amar; Cahill, Daniel; Sutherland, Garnette; Honeycutt, John; Jensen, Randy; Rich, Keith; Dowling, Joshua; Limbrick, David; Dacey, Ralph; Kim, Albert; et al.
Abstract: BACKGROUND: Few studies use large, multi-institutional patient cohorts to examine the role of intraoperative MRI (iMRI) in the resection of grade II gliomas. We assessed the impact of iMRI and other factors on overall survival (OS) and progression-free survival (PFS) for newly-diagnosed grade II astrocytomas and oligodendrogliomas. METHODS: Retrospective analyses of a multicenter database assessed the impact of patient-, treatment-, and tumor-related factors on OS/PFS. RESULTS: 232 resections (112 astrocytomas, 120 oligodendrogliomas; 135 males; mean age 36.2 ± 0.9 years) were analyzed. Oligodendrogliomas had longer OS (p< 0.001) and PFS (p=0.009) than astrocytomas. Multivariate regression showed that extent of resection (EOR), including gross-total (GTR) versus near-total (NTR) resection (p=0.02, HR: 0.64, 95% CI: 0.25-.79) and GTR versus subtotal resection (STR) (p=0.006, HR: 0.23, 95% CI: 0.08-0.66), was associated with longer OS. GTR versus NTR (p=0.04, HR: 0.49, 95% CI: 0.29-.85), GTR versus STR (p=0.02, HR: .54, 95% CI: .32-.91) and iMRI use (p=0.02, HR: 0.54, 95% CI: 0.32-0.92) were associated with longer PFS. Frontal (p=0.048, HR: 2.11, 95% CI: 1.01-4.43) and occipital/parietal (p=0.003, HR: 3.59, 95% CI: 1.52-8.49) locations were associated with shorter PFS (versus temporal). Kaplan-Meier analyses showed longer OS with increasing EOR (p=0.03) and 1p/19q gene deletions (p=0.02). PFS improved with increasing EOR (p=0.01), GTR versus NTR (p=0.02), and resections above STR (p=0.04). Factors influencing adjuvant treatment (35.3% of patients) included age (p=0.002, OR: 1.04) and EOR (p=0.037, OR: 0.41 for NTR versus STR; p=0.003, OR: 0.39 for GTR versus STR), but not glioma subtype or location, as determined by logistic regression. Additional tumor resection after iMRI was performed in 105/159 (66%) iMRI cases, yielding GTR in 54.5% of these cases. CONCLUSIONS: EOR significantly improves OS and PFS for patients with grade II astrocytomas and oligodendrogliomas. Intraoperative MRI may improve EOR and was associated with increased PFS.